Foreign bodies in the external auditory canal: A single center experience (Annals of Medical Research, 2021)
Aim: The aim of our study is to determine the risky age groups, to investigate what kind of materials may pose a danger and the measures that can be taken to prevent it and to evaluate the findings in the light of the literature.Materials and Methods: The medical records of patients diagnosed with foreign bodies in the external auditory canal admitted to Antalya Serik State Hospital Emergency Service or Ear-Nose and Throat (ENT) Clinic between January 2018 and December 2018 were retrospectively analyzed. Various parameters such as foreign bodies, age, sex, as well as clinical symptoms and treatment protocols were investigated, and these cases were discussed in the light of the literature.Results: A total of 96 patients admitted to our hospital at the time of the study. Fifty-four of them were male (56.25%) and 42 were female patients (43.75%). The mean age was 24.13 years (11 months - 76 years). Foreign bodies were removed from the right ear in 58 cases (60.4%), from the left ear in 35 cases (36.4%), and from both ears in 3 cases (3.1%). Most of the patients were preschool children aged between 0-5 years (n = 46, 47.9%). This patient group was followed by the adult-age patient group, who were 16 years old or older (n = 27, 28.1%). The most common foreign bodies in children were small plastic pieces (84.2%) and granular foods (76.5%). In adults, cotton swabs were the most common (71.4%). Conclusion: The presence of foreign bodies in the external auditory canal is a common problem in ENT diseases both in the pediatric group and in the adult group. Foreign bodies can cause complications even up to perforation in the ear. Parents should be made aware of not keeping small plastic pieces and granular foods near their children.
Keywords: Cotton swab; external auditory canal; foreign body